Efeitos do crédito do BNDES na sobrevivência das firmas brasileiras - Napole\~ao Luiz Costa da Silva; Alice Saccaro (Instituto de Pesquisa Econômica Aplicada (IPEA), 2019)
– This text evaluates the effect of the BNDES Finame credit program on the survival of Brazilian firms, separated according to their size, between 2002 and 2016. To this end, we employ the survival analysis method. In this work, we use the microdata bases of RAIS and BNDES financing operations. The results show that BNDES Finame has increased the average lifetime of micro, small and midsize companies. On the other hand, this credit program had no effect on the survival of large companies. In addition, the smaller the company, the greater the effect this type of credit has had on its lifetime. When it is analyzed other factors that have influence on the survival of micro-sized and small firms, it is found that participating in Simples Nacional rise their survival time, while the age - the older the company is - has a positive impact on the survival time of all companies.
Keywords: C10; E50; H81; 330; credit expansion; BNDES Finame; business survival; propensity score matching; survival analysis